Falsafah Perkerisan dalam Masyarakat Melayu. - Khamis Mohamad,; Nik Hassan Shuhaimi Nik Abdul Rahman; Abdul Latif Samian (2012)
As an invaluable artifact in the realm of Malay culture, the Keris stands as a philosophical and mysterious symbol in numerous fields including, but not limited to, the manucfacturing and forging process. The inimitable uniqueness is analysed through physical and non-physical attributes of the Keris that includes the distinctiveness of its remarkable strength, profound greatness, decorous standing in society, fearfulness and aspects of mystical elements synonymous with this relic. The philosophy of Keris is closely correlated to the creativity of the Empu in configuring the classification, structure, blade, anatomy, and pamor patency of the Keris.